Deotoritasi Guru di Era New Media - Ahmad Arif Ulin Nuha; Bambang Subahri (Bidayatuna, 2020)
The technological revolution causes changes in all aspects of life. It includes the educational spec. So that these changes also change all aspects in the world of education. One of the highlights in this paper is the relationship between teachers and students. The teacher initially becomes an important entity in the learning process. However, the presence of new media has replaced the teacher's position. It is no longer a central role in the educational process. Students have relied on gaining knowledge on technology. This phenomenon is contrary to the concept of Ahlussunnah Wal Jamaah education. Sanad continuity is an important thing in measuring the authenticity of knowledge. Not only that, the meaning of blessing is pinned on knowledge that has this sanad continuity. Seeing this phenomenon, the author assumes that technology has conducted teacher deauthorization in the education process of the new media era.